Why do drivers continue driving while fatigued? An application of the theory of planned behaviour. (April 2017) - Jiang, Kang; Ling, Feiyang; Feng, Zhongxiang; Wang, Kun; Shao, Cheng
Highlights: TPB was the fist used to predict drivers' fatigued driving behaviour. Subjective norms, perceived behaviour control and intentions show as significant predictors. Some useful suggestions were provide to modify drivers' fatigued driving behaviour. Abstract: Fatigued driving is one of the major contributors to road crashes around the world. To explore factors affecting fatigued driving behaviour from the perspective of social psychology, a questionnaire was designed based on the theory of planned behaviour. A sample of 214 drivers was examined. Drivers with poor sleep quality or a history of fatigue all showed a greater tendency to continue driving while fatigued, to have a more positive attitude towards driving while fatigued, and to perceive a higher level of control while driving fatigued. Furthermore, hierarchical multiple regression analysis showed overall support for the predictive utility of the theory of planned behaviour, accounting for 30.4% of the variance of fatigued driving behaviour after controlling for demographic variables. Overall, the results suggest that subjective norms, perceived behavioural control and intention have significant effects on self-reported continued driving while fatigued. Hence, a multiple-strategy approach should be utilized in addressing this issue.